Christ returns from the jungle : ayahuasca religion as mystical therapy - Blainey, Marc Gordon (State University of New York Press, 2021)
"An in-depth, ethnographic study of the transnational expansion of Santo Daime, a mystical religious tradition organized around sacramental ingestion of the mind-altering ayahuasca beverage. Explores the attraction of unconventional religions in the age of secularization"-- Provided by publisher
Keywords: Religion and culture -- Europe.; Santo Daime (Cult) -- Europe.; Cultural pluralism -- Europe.; Cultural pluralism -- Religious aspects.; Europe -- Religion -- 21st century.; Religion et culture -- Europe.; Santo Daime (Culte) -- Europe.; Diversité culturelle -- Europe.; Diversité culturelle -- Aspect religieux.; Cultural pluralism; Cultural pluralism -- Religious aspects; Religion; Religion and culture; Santo Daime (Cult); Europe; 2000-2099